Analisis buckling kolom bertulang dengan faktor pembesaran menggunakan SAP 2000: Studi Kasus : Hotel Bumi Nusantara - Rizal, Faiz; Defiana, Yanti; Martha, Taufik (Jurnal Ilmiah Teknik Sipil, 2025)
The stability of reinforced concrete columns is a critical aspect in the design of multi-story buildings, as failure due to buckling may trigger progressive collapse. The Indonesian Standard SNI 2847:2019 recommends the use of the moment magnification factor (δ) to account for slenderness effects, yet this manual approach is idealized and requires validation against more accurate numerical methods. This study aims to analyze the application of the moment magnification factor (δ) on reinforced concrete columns of the Hotel Bumi Nusantara structure and to evaluate its accuracy by comparing manual calculations with second-order nonlinear analysis using SAP2000 V22. The research involved first-order analysis, slenderness identification, eigenvalue buckling analysis, manual calculation of δ, and validation through second-order analysis. The results show that all columns have a slenderness ratio ≤ 22 and buckling factors (λcr) greater than 25, indicating very stable global conditions. Manual calculations produced δ values ranging from 1.052 to 1.056, with moment magnification of approximately 5%. However, validation revealed significant discrepancies with second-order analysis, particularly in the major-axis moments, with differences reaching up to –159%. It can be concluded that the moment magnification factor (δ) provides a conservative initial estimate, but second-order nonlinear analysis offers a more realistic basis for determining final design moments to ensure both safety and efficiency of the structure.